A comparison of methods of plasmapheresis for the treatment of late antibody mediated rejection in kidney transplant recipients. Issue 3 (14th October 2022) - Caliskan, Yasar; Mirioglu, Safak; Dirim, Ahmet Burak; Ozluk, Yasemin; Yegit, Ozan; Aksoy, Elif; Safak, Seda; Guller, Nurana; Demir, Erol; Artan, Ayse Serra; Oto, Ozgur Akin; Besisik, Sevgi; et al.
Abstract: Introduction: We compared the outcomes associated with plasma exchange (PE), double filtration plasmapheresis (DFPP), or immunoadsorption (IA) in the treatment of late antibody mediated rejection (AMR). Methods: Sixty‐nine kidney transplantation (KTx) recipients with late AMR were retrospectively categorized according to management with PE ( n  = 30), DFPP ( n  = 22) or IA ( n  = 17). Allograft loss was compared across treatment groups by Kaplan–Meier analysis and Cox regression. Results: Study groups were similar regarding age, sex, donor type, kidney function, donor specific antibodies, and post‐KTx follow‐up time. Five‐year graft survival trended higher with IA (70.6%) compared to PE (36.7%) and DFPP (27.3%) ( p  = 0.06). In multivariate Cox regression, baseline eGFR (HR per ml/min/1.73 m 2 [95% CI]; 0.96 [0.94–0.99]), rituximab use (HR [95% CI]; 0.42 [0.21–0.84]), interstitial inflammation (i) (HR [95% CI]; 2.05 [1.13–3.69]), and transplant glomerulopathy (cg) (HR [95% CI]; 1.46 [1.13–1.87]) were associated with graft loss. Conclusion: These results motivate the need for continued assessment of rituximab and plasmapheresis in larger studies.